2021
DOI: 10.1016/j.jbc.2021.100315
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycerophospholipid flipping and P4-ATPases in Toxoplasma gondii

Abstract: Lipid flipping in the membrane bilayers is a widespread eukaryotic phenomenon that is catalyzed by assorted P4-ATPases. Its occurrence, mechanism, and importance in apicomplexan parasites have remained elusive, however. Here we show that Toxoplasma gondii , an obligate intracellular parasite with high clinical relevance, can salvage phosphatidylserine (PtdSer) and phosphatidylethanolamine (PtdEtn) but not phosphatidylcholine (PtdCho) probes from its milieu. Consistently, the drug analogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 95 publications
2
23
0
Order By: Relevance
“…Here we demonstrate that T. gondii encodes for 6 type IV ATPases and 4 CDC50 cofactors with different functions and fitness associated to their deletion. Importantly, some of the data presented here are supported by an overlapping study (30).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Here we demonstrate that T. gondii encodes for 6 type IV ATPases and 4 CDC50 cofactors with different functions and fitness associated to their deletion. Importantly, some of the data presented here are supported by an overlapping study (30).…”
Section: Discussionsupporting
confidence: 82%
“…During this process, the transmembrane region remainsstructurally rigid based on its interaction with the CDC50 partner (27). Among the repertoire of P4-ATPases in apicomplexan parasites, some are essential for parasite survival (28)(29)(30) yet little is known about their biological roles and enzymatic functions. Beside the lipid composition, membrane fusion is a universal process that also involves a machinery composed of SNAREs (for "soluble N-Ethylmaleimide-sensitive factor (NSF)-attachment protein receptor") (31).…”
Section: Introductionmentioning
confidence: 99%
“…These polar headgroups are used by the parasite for the production of phosphatidylserine (PS), phosphatidylethanolamine (PE), and phosphatidylcholine (PC) [ 55 , 74 ]. Chen and colleagues have shown that PE and PS are able to be taken up directly from the host environment, unlike PC that thus has to be generated directly by the parasite from host-scavenged and or de novo–made precursors [ 75 ]. A very recent study suggests that parasite lysophopholipase could be used to generate the phosphocholine for parasite PC synthesis from existing lysolipids from the host during P .…”
Section: Lipid Scavenging Mechanismsmentioning
confidence: 99%
“…Both proteins under starvation showed no deleterious effect on tachyzoite growth, indicating it is unlikely they are involved in nutrient adaptation. ATP-dependent PL transporters for PS and PE are present in the plasma membrane of tachyzoites [ 75 ].…”
Section: Lipid Scavenging Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation